â€œThe Hopes, the Aspirations, the Guilt Embedded in Our Shaken Livesâ€: Romesh Gunesekeraâ€™s Noontide Toll - Perera, Senath Walter (Asiatic: IIUM Journal of English Language and Literature, 2017)
The fiction of Sri Lankan diasporic writer Romesh Gunesekera has generated considerable debate among critics. While some accuse him of pursuing an Orientalist agenda to the extent of being a native informant; others, especially those residing in the West, have lauded him for faithfully depicting the socio-political climate that prevailed in Sri Lanka. The two decades that have elapsed since the publication of Reef, however, have witnessed a subtle transformation in his fiction and in criticsâ€™ response to the same. Noontide Toll (2014), which is Gunesekeraâ€™s first work on Sri Lanka since the cessation of the war, is more contemplative than exotic, and his critique of the island largely understated rather than explicit. Eschewing the controversial strategy of privileging the country of adoption over that of origin which some accused him of in Reef, Gunesekera here makes his narrator Vasantha exploit the post-war obsession for travel to transport in his van local and foreign customers who are scarred by their past and negotiate the present with uncertainty as they contemplate the need to construct a future. By having many of his characters in this work adopt a more philosophical approach to life, in making subtle adjustments to his authorial strategies, and in showing a willingness to treat the multifarious issues currently faced by the nation in a nuanced and in-depth manner, the author has succeeded in â€œneutralisingâ€ the debate on his work.